Determinación de las isotermas de adsorción del polvo atomizado de Bixa Orellana L. (achiote) - Koo del Aguila, Diego Walker (2022)
In the present investigation, the effect of temperature on bixin was evaluated by means of drying kinetics, for which a series of steps were carried out, such as drying kinetics in a tray dryer by forced convection applying the 2 factorial design.3 to represent the minimum and maximum values at temperatures of 50 °C and 70 °C combining it with air speeds of 3m/s and 5 m/s and a bed thickness of 3mm and 5mm respectively. Bixin contents of 7.98 mg/100g m.s. were found at temperatures of 50 °C and 70 °C, maintaining constant air velocity and bed thickness, this result indicates that bixin is not affected at these temperatures, the rate of drying increased from 1.36 kg/h m2 at a temperature of 50 °C up to 3.79 kg/h m2 for a temperature of 70 °C indicating a higher mass transfer due to the direct influence of temperature, followed by the dry seeds ofBixa orellana L were ground and turned into flour to evaluate their adsorption isotherms, the mathematical models B.E.T. and G.A.B using the salts of sodium chloride and potassium iodide at temperatures of 20 °C, 25 °C and 30 °C finding values of water activities (aw) ranging from 0.67 to 0.69 for the mathematical model of B.E.T with sodium chloride and values from 0.87 to 0.64 for the G.A.B mathematical model, for potassium iodide 0.76 to 0.64 for the B.E.T model and 0.77 to 0.64 for the G.A.B model, the activation energy at these temperatures was also determined with the Arrhenius equation Ea= 28299.19 j/mol k, finally its useful life time (TVU) of the flour was projected, having the peroxide index as a quality reference that must be less than 5 mEq/kg, obtaining that at 20 °C will last 34.75 months, 25 °C will last 33.75 months and at 30 °C it will last 33.25 months. With the data obtained, it can be concluded that the drying period at decreasing speed takes the longest drying time and the constant drying period was very short.